Bahan Ajar E-Book Berbentuk Flipbook Model PjBL Meningkatkan Hasil Belajar Pendidikan Pancasila - Maulidya, Salma; Aeni, Kurotul (Jurnal Pendidikan dan Pengajaran, 2024)
Teachers need to develop digital teaching materials optimally, and the learning models used are less varied, resulting in low student learning outcomes. The intent of this research is to establish e-book teaching materials in the kind of flipbooks using the PjBL model, with the intention of enhancing the learning outcomes of Pancasila Education. This type of research is research and development (R&D) using the ADDIE model. The subjects of this research are 1 learning material expert and 1 learning media expert. The test subjects are 28 students. The data collection methods used include both test and non-test methods (interviews, observation, questionnaires, and documentation). The research data collection instruments were interview sheets, questionnaires, and multiple-choice questions. The methods used during data analysis are qualitative descriptive analysis and quantitative and inferential statistics. The research results were that the assessment from material expert was 88.8% (very feasible), and media expert had a percentage of 93.3% (very feasible). The t-test results show disparities in student learning outcomes after using e-book teaching materials in flipbooks in the PjBL model. The N-Gain test results were within the high category. The conclusion was reached that e-book teaching materials in the kind of flipbooks in the PjBL model are very feasible and practical to apply in the learning process to posper student learning outcomes in the Class IV Pancasila Education subject on Indonesian cultural diversity.